Van der Waals epitaxial growth and optoelectronics of large-scale WSe2/SnS2 vertical bilayer p–n junctions. Issue 1 (December 2017) - Yang, Tiefeng; Zheng, Biyuan; Wang, Zhen; Xu, Tao; Pan, Chen; Zou, Juan; Zhang, Xuehong; Qi, Zhaoyang; Liu, Hongjun; Feng, Yexin; Hu, Weida; Miao, Feng; et al.
Abstract High-quality two-dimensional atomic layered p–n heterostructures are essential for high-performance integrated optoelectronics. The studies to date have been largely limited to exfoliated and restacked flakes, and the controlled growth of such heterostructures remains a significant challenge. Here we report the direct van der Waals epitaxial growth of large-scale WSe2 /SnS2 vertical bilayer p–n junctions on SiO2 /Si substrates, with the lateral sizes reaching up to millimeter scale. Multi-electrode field-effect transistors have been integrated on a single heterostructure bilayer. Electrical transport measurements indicate that the field-effect transistors of the junction show an ultra-low off-state leakage current of 10−14 A and a highest on–off ratio of up to 107 . Optoelectronic characterizations show prominent photoresponse, with a fast response time of 500 μs, faster than all the directly grown vertical 2D heterostructures. The direct growth of high-quality van der Waals junctions marks an important step toward high-performance integrated optoelectronic devices and systems. Growth of large area and defect-free two-dimensional semiconductor layers for high-performance p–n junction applications has been a great challenge. Yang et al. prepare millimeter-scaled WSe2 /SnS2 vertical heterojunctions by two-step van der Waals epitaxy, which show excellent optoelectronic properties.